Quantitative Analysis of the Roots, Stems, and Leaves of Polygonum multiflorum by Ultra-High-Performance Liquid Chromatography–Mass Spectrometry. (24th July 2018) - Rui, Wen; Xia, Wanxia; Zhao, Wei; Li, Bingling; Li, Jian; Feng, Yifan; Chen, Hongyuan; Zhao, Shujin
ABSTRACT: The concentrations of 2, 3, 5, 4′-tetrahydroxystilbene-2- O -β-d-glucoside, quercetin, catechin, emodin, and polygoacetophenoside in roots, stems and leaves of Polygonum multiflorum, a traditional Chinese medicinal herb, were simultaneously determined by ultra-performance liquid chromatography equipped with electrospray ionization and quadrupole-time-of-flight mass spectrometry (UPLC/ESI-Q-TOF-MS). The established quantitative analysis method has good precision (<2.94%), accuracy (97.21–101.37%), linear correlation coefficient (<0.990), and high sensitivity (0.46 ng/mL). The concentrations of 2, 3, 5, 4′-tetrahydroxystilbene-2- O -β-d-glucoside and emodin were 34.86 ± 10.58 and 31.09 ± 8.26 mg/g, respectively, in the roots, much higher than that in the stems and leaves, while the concentration of catechin (29.62 ± 7.76) was the highest in stems. However, polygoacetophenoside and quercetin are the main components in the leaves: 50.54 ± 12.24 and 28.35 ± 1.88 mg/g, respectively. The results show that these concentration differences in roots, stems and leaves of P. multiflorum may be associated with the therapeutic effects of this traditional Chinese medicinal herb. This method may be used for the quality evaluation of the different components of P. multiflorum .